Relación entre la constitución de micro y pequeñas empresas y los créditos empresariales en el departamento de Loreto 2021-2024 - Aguilar Ferreira, Alvaro Paolo (2025)
Understanding the relationship between access to credit and the stablish of micro and small enterprise is crucial to designing policies and programs that promote business development. This approach has the potential to improve the living conditions of the inhabitants, reduce poverty and promote economic equity. The present investigation considered as the study population 42 monthly records corresponding to the micro and small enterprise established with tax domicile in the department of Loreto as well as the business loans granted by the financial system at the end of each month during the period between January 2021 and June 2024. In this context, a very strong direct relationship of 95.41% was identified between the constitution of micro and small enterprise and business loans given by financial companies. Similarly, a very strong direct relationship of 92.32% was found between the constitution of micro and small enterprise and business loans given by municipal savings banks. Contrarily, no positive relationship was found between the establishment of micro and small enterprise and business loans given by commercial banks.